Ecotoxicology assessments in avian species using cell-based models: A review. Issue 4 (November 2021) - Ball, Ashley L.; Lavado, Ramon
Cell-based models in avian species have historically focused on virology due to the demands of animal agriculture and vaccine production industries. Recent years have witnessed a gradual rise in the use of these models ( in ovo, cell lines, primary cell cultures, organ slices, and organ-on-a-chip) in ecotoxicological studies as scientists and governments begin the shift to new approach methodologies, a shift validated by the recent memo by the Environmental Protection Agency announcing the end of mammalian testing in the next two decades. This rise has been hindered by the limited standards available for avian species and the unknowns surrounding cell-based assay applicability in extrapolation to in vivo . Toxicologists have incorporated these models in many different studies, including maternal deposition, mechanistic, metabolic, and non-target analysis methods, demonstrating the broad utility of cell-based assays. In ovo methods are ideal for reproductive and early life stage development studies, primary cell cultures for metabolic analysis, cell lines for long term studies requiring culture, organ slices for metabolic research, and organ-on-a-chip models for predictive analysis. These models all have their limitations that researchers need to consider when choosing which is most appropriate for the intended research, however. The current indications are that future avian cell-based model testing would benefit from expanding the species diversity available in cell lines and increasing metabolic conservation in full replacement methods. In ovo and primary cell culture methods should also be examined to increase efficiency and further reduce animal usage. This review examines the use, limitations, and published applications of these models in an ecotoxicological context to understand the current state of avian cell-based models to explain what future directions should be taken and how best to apply the methods available to current problems that avian researchers are approaching.